Hambatan Pengelolaan Kadar Gula Darah pada Pasien Diabetes Melitus Tipe 2 - Alisarjuni Padang; Mula Tarigan; Rina Amelia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study explores various barriers to managing Blood Sugar Levels (KGD) in type 2 DM patients. The method used is a systematic review by browsing articles in the ScienceDirect, Ebsco, PubMed, CINAHL and PMC databases selected based on the PRISMA diagram. The results showed that some barriers to blood sugar management were related to limited costs, poor medication adherence, common knowledge and management of type 2 diabetes, patient psychosocial factors and patient activity factors. In conclusion, the type of obstacle that is most often found related to the management of diabetes mellitus is the lack of knowledge about DM and its management, both patients and health workers. Keywords: Type 2 DM, Management Barriers, Knowledge Improvement